Establishment of visual assessment for the severity of dark circles in Chinese Han women. Issue 6 (17th May 2021) - Tan, Yimei; Jiang, Yanwen; Chen, Jiaping; Sun, Hua; Qiu, Yuchen
Abstract: Objective: To establish a visual assessment scale for the severity of dark circles' pigmented and vascular type in Chinese women. Materials and method: A total of 269 healthy Chinese women from Shanghai with different degrees of dark circles', both pigmented and vascular types, were evaluated by visual assessment. Photographs of their dark circles were analyzed by image analysis. Results: The visual assessment evaluation on classification and severity showed a favorable agreement between the successive measured results. Significant differences from very slight to severe dark circles for pigmented type and vascular type were observed. The severity level by visual assessment was significantly positively correlated with ΔE values while negatively correlated with ΔL values ( P  < .01) in both pigmented and vascular types. Besides, Δa values of vascular type were significantly positively correlated with the ΔE values for dark circles' vascular type. Values between ΔE and ΔL also showed a significant negative correlation ( P  < .01). Conclusion: The five‐point visual assessment scale for dark circles of vascular and pigmented types was verified and proved to have good repeatability. The image analysis's objective result proved significant and consistent with the visual assessment and color parameters. This scale could be a useful and effective tool in diagnosing dark circles' severity.